2016
DOI: 10.3171/2015.2.jns141889
|View full text |Cite
|
Sign up to set email alerts
|

Timing of the resumption of antithrombotic agents following surgical evacuation of chronic subdural hematomas: a retrospective cohort study

Abstract: C hroniC subdural hematoma (cSDH) is a disease of the elderly and demonstrates an incidence of approximately 3.4 patients per 100,000 persons younger than 65 years of age and 8 to 58 patients per 100,000 persons older than 65 years. 1,4,9 The prevalence of cSDH is expected to rise as the percentage of the United States population older than 65 years grows from 12% in 2003 to a projected 20% by 2030. 17Other identified risk factors for the development of cSDH include male sex, history of falls, chronic alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…24,27 Early ASA resumption or even continued perioperative intake was shown to be safe for burr-hole drainage in chronic subdural hematoma (cSDH) as well as shunt placement. 9,10,14,15,17 To our knowledge, there are no randomized controlled trials (RCTs) analyzing bleeding risk with continued perioperative AP/AC treatment in neurosurgery. A protocol for an ongoing RCT of continued ASA treatment for patients undergoing surgical evacuation of cSDH has been published and the study is currently ongoing.…”
Section: Management Of Ap/ac Treatment In Neurosurgical Patientsmentioning
confidence: 99%
“…24,27 Early ASA resumption or even continued perioperative intake was shown to be safe for burr-hole drainage in chronic subdural hematoma (cSDH) as well as shunt placement. 9,10,14,15,17 To our knowledge, there are no randomized controlled trials (RCTs) analyzing bleeding risk with continued perioperative AP/AC treatment in neurosurgery. A protocol for an ongoing RCT of continued ASA treatment for patients undergoing surgical evacuation of cSDH has been published and the study is currently ongoing.…”
Section: Management Of Ap/ac Treatment In Neurosurgical Patientsmentioning
confidence: 99%
“…Of the remaining 17 articles, 9 were excluded because they were only about anticoagulants [24][25][26][27][28][29][30][31][32], one was excluded because the majority of participants who had resumed antithrombotic agents had their medicine terminated or changed during the follow-up [33], and one was excluded because there was no clear record of which kind of antithrombotic agents, oral anticoagulant, or AP therapy was resumed [34]. Finally, only 6 articles met the inclusion criteria [35][36][37][38][39][40]. The study selection is presented in flow chart form in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…The 6 studies offered data containing 1916 patients (825 in AP resumption group, 1091 in non-AP resumption group) [35][36][37][38][39][40]. Pooled result using the random-effects model showed that there was no significant difference between AP resumption group and non-AP resumption group for ICH recurrence or hematoma expansion (RR, 0.84; 95% CI, 0.47-1.51; P = 0.56) (Fig.…”
Section: Ap Resumption Did Not Significantly Increase Ich Recurrence mentioning
confidence: 99%
“…One retrospective cohort study compared outcomes in those who restarted on their antithrombotic drugs to those who did not. 3 The researchers found similar risks of thromboembolism (unadjusted OR, 1.34; 95% CI, 0.29-6.13), but a lower risk of recurrence (unadjusted OR, 0.06; 95% CI, 0.02-0.20) in the antithrombotic restart group. This result, however, is limited by few outcome events in the study group and likely confounders that were not adjusted for.…”
Section: Discussionmentioning
confidence: 95%
“…1 Approximately 40% of patients with CSDH are taking an antithrombotic drug at the time of presentation. 2,3 A large, population-based case-control study has demonstrated an association between increasing antithrombotic drug use and increasing incidence of CSDH. 4 Perioperative management of antithrombotic drugs is therefore an important aspect for these patients.…”
Section: Introductionmentioning
confidence: 99%